Feasibility and Safety of Perilla Seed Oil as an Additional Antioxidative Therapy in Patients with Mild to Moderate Dementia - Chuntida Kamalashiran; Junya Pattaraarchachai; Sombat Muengtaweepongsa (Journal of Aging Research)
Dementia is a broad-spectrum terminology for a degenerate in cognitive function severe enough to intervene in activities of daily living. Oxidative stress plays a major role in the neurodegenerative cascade, leading to the irreversible mechanism in dementia. Perilla seed oil is extracted from its seeds and contains a high source of antioxidative substances such as omega-3 fatty acid. With its prominent antioxidative property, perilla seed oil demonstrates neuroprotective effects against dementia in preclinical studies. We aim to prove the feasibility and safety of perilla seed oil as an additional antioxidative therapy in patients with dementia. This single-centered, double-blinded, placebo-controlled trial randomized 239 patients with clinical diagnosis of mild to moderate dementia according to the Thai Mini-Mental State Examination (TMSE) score of 10 to 23 or the Thai Montreal Cognitive Assessment score of 12 to 25. Either two capsules containing 500 milligrams of perilla seed oil or similarly appearing two capsules containing 500 milligrams of olive oil (placebo) four times daily was added to conventional standard treatment of dementia for six months. Clinical side effects and routine laboratory results at baseline and after treatment were compared between both groups. Nausea and vomiting were the most common clinical side effects (3%) found equally in both groups. Three patients in the placebo group prematurely discontinued the medication, while only one patient in the treatment group quit the medication early. However, about 5% of patients in both groups could not comply with the regimen of the treatment. The routine laboratory results, including complete blood counts, kidney function tests, and liver function panels, at baseline and after treatment, were not significantly different in both groups. In conclusion, perilla seed oil was feasible and safe to add on with standard treatment in patients with mild to moderate dementia. Further study is needed to confirm its benefit to use as additional antioxidative therapy in patients with dementia.